2001
DOI: 10.1080/713602836
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual irregularity in the first postmenarchal years: an early clinical sign of polycystic ovary syndrome in adolescence

Abstract: We determined the hormonal, metabolic and ultrasonographic pattern of adolescents with menstrual irregularity since menarche but without clinical signs of hyperandrogenism with the aim of evaluating whether this condition represents an early stage of polycystic ovary syndrome (PCOS). These adolescents were divided in two groups: 13 adolescents with irregular cycles (IC) within the first 3 postmenarchal years (IC < or = 3) and 15 adolescents having persistent irregular cycles for more than three postmenarchal y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Two thirds of adolescents whose oligomenorrhea persisted for 2 or more years still have oligomenorrhea 10 years later [39, 40]. Avvad et al [41] reported that menstrual irregularity within the first postmenarchal years can be an early clinical sign of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Two thirds of adolescents whose oligomenorrhea persisted for 2 or more years still have oligomenorrhea 10 years later [39, 40]. Avvad et al [41] reported that menstrual irregularity within the first postmenarchal years can be an early clinical sign of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, menstrual irregularities within the first years after menarche can be considered as an early clinical sign of PCOS [14]. Based on another study [12], the occurrence of PCOS increased significantly with irregularities in the menstrual cycle pattern.…”
Section: Discussionmentioning
confidence: 99%
“…65 To some extent this is because the adolescent ovary may normally have a multifollicular appearance, 58,71 but many meet current polycystic follicle count criteria. 52,64,6668 Furthermore, several studies indicate that ovarian volume during adolescence is larger than that of the normal adult: for example, the median for the normal upper limit of mean ovarian volume during adolescence according to studies to date approximates 12 cc (Table 5). 52,56,6670,72,73 Thus, application of adult criteria for PCOM to adolescents seems very problematic.…”
Section: Discussionmentioning
confidence: 99%